International Society for Gynecologic Endoscopy (ISGE) guidelines and recommendations on gynecological endoscopy during the evolutionary phases of the SARS-CoV-2 pandemic (2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has raised some important interrogations on minimally invasive gynaecological surgery. The International Society for Gynecologic Endoscopy (ISGE) has taken upon itself the task of providing guidance and best practice policies for all practicing gynaecological endoscopists. Factors affecting decision making processes in minimal invasive surgery (MIS) vary depending on factors such as the phase of the pandemic, policies on control and prevention, expertise and existing infrastructure. Our responsibility remains ensuring the safety of all health care providers, ancillary staff and patients during this unusual period. We reviewed the current literature related to gynecological and endoscopic surgery during the Coronavirus Disease 19 (COVID-19) crisis. Regarding elective surgery, universal testing for SARS-CoV-2 infection should be carried out wherever possible 40 h prior to surgery. In case of confirmed positive case of SARS-CoV-2, surgery should be delayed. Priority should be given to relatively urgent cases such as malignancies. ISGE supports medical optimization and delaying surgery for benign non-life-threatening surgeries. When possible, we recommend to perform cases by laparoscopy and to allow early discharges. Any procedure with risk of bowel involvement should be performed by open surgery as studies have found a high amount of viral RNA (ribonucleic acid) in stool. Regarding urgent surgery, each unit should create a risk assessment flow chart based on capacity. Patients should be screened for symptoms and symptomatic patients must be tested. In the event that a confirmed case of SARS-CoV-2 is found, every attempt should be made to optimize medical management and defer surgery until the patient has recovered and only emergency or life-threatening surgery should be performed in these cases. We recommend to avoid intubation and ventilation in SARS-CoV-2 positive patients and if at all possible local or regional anesthesia should be utilized. Patients who screen or test negative may have general anesthesia and laparoscopic surgery while strict protocols of infection control are upheld. Surgery in screen-positive as well as SARS-CoV-2 positive patients that cannot be safely postponed should be undertaken with full PPE with ensuring that only essential personnel are exposed. If available, negative pressure theatres should be used for patients who are positive or screen high risk. During open and vaginal procedures, suction can be used to minimize droplet and bioaerosol spread. In a patient who screens low risk or tests negative, although carrier and false negatives cannot be excluded, laparoscopy should be strongly considered. We recommend, during minimal access surgeries, to use strategies to reduce production of bioaerosols (such as minimal use of energy, experienced surgeon), to reduce leakage of smoke aerosols (for example, minimizing the number of ports used and size of incisions, as well as reducing the operating pressures) and to promote safe elimination of smoke during surgery and during the ports’ closure (such as using gas filters and smoke evacuation systems). During the post-peak period of pandemic, debriefing and mental health screening for staff is recommended. Psychological support should be provided as needed. In conclusion, based on the existent evidence, ISGE largely supports the current international trends favoring laparoscopy over laparotomy on a case by case risk evaluation basis, recognizing the different levels of skill and access to minimally invasive procedures across various countries.